The British Crown in the Spotlight of Literary and Cultural Studies: Analyzing Past and Present ‘Myths of the Monarchy’ (KULT_online, 2018)
Anette Pankratz and Claus-Ulrich Viol’s edited volume (Un)making the Monarchy comprises eleven articles that aim at analyzing (contemporary) phenomena surrounding the British monarchy in cultural fields as varied as fashion, literature, satire, or anti-monarchist political tendencies. With its prevailing cultural and literary studies perspectives, the volume addresses in an innovative way timely and pressing questions in the field of royal studies, among them the question for the reason of the unrelenting appeal of this ancient institution. Despite an overall constructivist stance, the articles in the volume draw on very concrete socio-cultural, socio-political, and even psychological effects that the “myths of monarchy” (p. 17) have on contemporary British society.